The Relationship Between Nurses' Workload and Quality of Service to Patients in the ICU Room - Rahmawati Shoufiah; Jenti Sitorus; Wibowo Hanafi Ari Susanto; Rida Millati; Herna Linda (CV. Get Press Indonesia, 2025)
Health services in the ICU room have a high level of complexity, with nurses as the main medical personnel who play a role in providing intensive care to patients in critical condition. High workload in nurses can affect the quality of service provided. This study aims to analyze the relationship between nurse workload and quality of service to patients in the ICU room. This research method uses a correlational design with a cross-sectional approach. The study sample amounted to 50 nurses in the ICU room of RSUD Abdul Wahab Sjahranie Samarinda who were selected using purposive sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that the majority of nurses had a moderate workload (68%), while the quality of service provided was mostly classified as good (92%). Statistical analysis showed a significant relationship between workload and service quality (p-value = 0.000), where nurses with heavy workloads were more at risk of experiencing a decrease in service quality. These results indicate that effective workload management is necessary to maintain quality of care in the ICU. Hospital management is advised to evaluate work distribution to optimize nurse performance and improve the quality of health services.